HAMLET and synthetic derivatives as pre-operative agents in the treatment of oral and oesophageal cancer - Ghanim, Magda (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2020)
Oral and oesophageal cancers are aggressive tumours that are frequently diagnosed late, with high morbidity, mortality, and difficulties in surgical and therapeutic intervention. Novel imaging probes could assist in early diagnosis and alleviate treatment complications through demarking a clear margin for resection during surgery. A further need exists for effective and selective neoadjuvant therapies that reduce tumour size before surgery. This project addresses both issues by clarifying the mechanism of action of a class of natural anti-cancer protein-fatty acid complex agents derived from milk and by creating a synthetic polymer-fatty acid derivative as a probe for cancer cell identification. The novel probe was designed to be fluorescent and comprises natural component molecules found in milk and wheat. The probe s characteristics were investigated in SCC-9 cells - a squamous cell carcinoma of the tongue. The synthesised probe was shown to be non-toxic, and actively taken up, internalised, and expelled by cells by flow cytometry, confocal and multiphoton microscopy and fluorescence spectroscopy. An examination of the uptake mechanism revealed that the molecule is internalised via receptor-mediated endocytosis. The relevance of the probe for cancer cell identification was shown through inhibition of the molecule s uptake with a monoclonal antibody against the CD44 receptor, a key marker of cancer stem cell status, metastasis, and cancer progression. HAMLET (Human Alpha-lactalbumin Made Lethal to Tumour cells) and its bovine analogue BAMLET (Bovine Alpha-lactalbumin Made Lethal to Tumour cells) are protein-fatty acid complexes that display toxicity toward cancers of different origin, while most primary non-cancer cells remain resistant. We show that metabolism is important for their selective therapeutic potential against cancer cells and that BAMLET toxicity can be modulated through metabolic changes. Differentiation of SCC-9 cells significantly increased cellular resistance, whereas adaptation to culturing in galactose conditioned medium greatly sensitized the cells to BAMLET, and the effect was reversable by glucose addition. Metabolic and cellular uptake studies suggested a link between glycolytic activity, endocytic traffic, and BAMLET sensitivity. Through endocytosis inhibition studies, macropinocytosis was shown to be BAMLET s point of entry into SCC-9 cells. This discovery could lead to further developments resulting in improved fatty-acid containing complex based neoadjuvant therapeutics.
APPROVED
Keywords: HAMLET, neoadjuvant therapy, oral cancer, esophageal cancer, cancer imaging